2015
DOI: 10.3823/1610
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis access: clinical and epidemiological profile of patients and their vascular access in interior of Brazil

Abstract: Background: The analysis of vascular access for haemodialysis is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this study, having a catheter as the first access and an unplanned HD start were associated with a higher risk of death within 5 years. Other studies also found high rates of NTC use in Brazilian public health patients ( 13 ). According to our findings, public health insurance may possibly affect the type of prevalent vascular access, increasing the chance of having an NTC and reducing the chance of TC use.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, having a catheter as the first access and an unplanned HD start were associated with a higher risk of death within 5 years. Other studies also found high rates of NTC use in Brazilian public health patients ( 13 ). According to our findings, public health insurance may possibly affect the type of prevalent vascular access, increasing the chance of having an NTC and reducing the chance of TC use.…”
Section: Discussionmentioning
confidence: 82%